2012
DOI: 10.1890/110194
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐population evidence of oriented chain migration in northern gannets (Morus bassanus)

Abstract: International audienceAlthough oriented migrations have been identified in many terrestrial bird species, the post-breeding-season movements of seabirds are generally regarded as dispersive. We used geolocator tags to reveal post-breeding movements and winter distribution of northern gannets (Morus bassanus) at a meta-population scale. By focusing on five breeding colonies of European gannets, we show that their breeding and wintering grounds areconnected by a major flyway running along the coasts of Western E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
88
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(93 citation statements)
references
References 23 publications
5
88
0
Order By: Relevance
“…It could be hypothesized that these two groups of birds came from two distinct breeding colonies and that ompA variants could be used as markers of their origin. Thus, taking into account that the northern gannet is a species breeding in colonies with seasonal and age distinct patterns of distributions (60)(61)(62)(63), adults collected in the summer in our study harbored one or another of the two ompA variants and came then probably from mixed groups of birds whose breeding colonies were located in the Channel or on the south coasts of Great Britain or Ireland (Celtic Sea) (62). To confirm the potential of the chlamydial typing for the colony determination and then for ecological studies of the northern gannet species, analysis of Chlamydiaceae species harbored by birds from different breeding colonies across Europe would be interesting.…”
Section: Discussionmentioning
confidence: 99%
“…It could be hypothesized that these two groups of birds came from two distinct breeding colonies and that ompA variants could be used as markers of their origin. Thus, taking into account that the northern gannet is a species breeding in colonies with seasonal and age distinct patterns of distributions (60)(61)(62)(63), adults collected in the summer in our study harbored one or another of the two ompA variants and came then probably from mixed groups of birds whose breeding colonies were located in the Channel or on the south coasts of Great Britain or Ireland (Celtic Sea) (62). To confirm the potential of the chlamydial typing for the colony determination and then for ecological studies of the northern gannet species, analysis of Chlamydiaceae species harbored by birds from different breeding colonies across Europe would be interesting.…”
Section: Discussionmentioning
confidence: 99%
“…The at-sea area used by Bugio petrels during this stage seems to overlap with the distribution of Zino's petrels Pterodroma madeira from Madeira (Zino et al 2011), Cory's shearwater Calonectris diometea from Desertas (Paiva et al 2010a) and Selvagens (Paiva et al 2010c), and Cape Verde shearwater Calonectris edwardsii from Cape Verde (Roscales et al 2011). The African shelf area along the coast of Mauritania appears to be very important for populations of these 4 seabird species for part or all of the year and also for migrant seabirds from elsewhere, including Sabine's gull Larus sabini (Kopp et al 2011), northern gannet Morus bassanus (Stenhouse et al 2012), great skua Stercorarius skua (Magnusdottir et al 2012) and south polar skua S. maccormicki (Fort et al 2012). In fact, this area is within one of the most important large marine ecosystems in the world -the Canary Current -with strong and nutrient-rich upwelling, which naturally elevates primary productivity and progressively increases the abundance of plankton and small planktivorous pelagic fish, cephalopods and crustaceans, which ultimately attracts seabirds to the area (Mann & Lazier 2006, Sherman & Hempel 2009).…”
Section: Habitat Use During the Breeding Stagementioning
confidence: 99%
“…Successful deployments on breeding Gannets include geolocator loggers (Kubetzki et al 2009, Fort et al 2012, satellite PTTs (Hamer et al 2000, Langston & Teuten 2012, GPS loggers and bird-borne cameras (Wakefield et al 2013. These tracking studies demonstrate that Gannets are very suitable birds for deployment and recovery of devices.…”
Section: Tracking Movements Of Adultsmentioning
confidence: 99%
“…Colour rings can be read on birds as they stand at, walk to, or depart from the nest, but can be difficult to see on incubating birds. Researchers deploying geolocation data loggers on breeding Gannets have found that a very high proportion of loggers can be recovered from adults the following breeding season (Kubetzki et al 2009, Fort et al 2012, so there is every reason to think that a high proportion of colour ringed adults could be resighted each year at colonies where some birds are accessible. Bass Rock, a key site close to proposed offshore wind farms, was especially suitable for such work as the Gannets there are used to seeing people visiting the colony, and large numbers could in the past be approached safely on the top of the island.…”
Section: Can Survival Rates Of Gannets Be Measured Accurately?mentioning
confidence: 99%
See 1 more Smart Citation